Sociodemographic and gestational factors of adolescent mothers associated with prematurity - Camila Amthauer; Maria Luzia Chollopetz da Cunha (Universidade Federal do Ceará, 2022)
Objective: to analyze the sociodemographic and gestational factors of adolescent mothers associated with prematurity. Methods: quantitative, cross-sectional, retrospective, and analytical study, developed with 488 adolescent mothers and their respective 489 newborns. Data were collected by query and analyzed using the SPSS. To verify the association between variables, the Chi-square or Fisher's exact test was used. To control for confounding factors, the multivariate Poisson Regression model was used. Results: adolescent mothers were mostly single, with occupation and education inadequate for their age; 76.5% did not have prenatal care appropriate for gestational age. The prevalence of prematurity was 6.6% and was associated with the number of adequate prenatal visits, twin pregnancy, and vaginal delivery. Conclusion: prematurity was associated with the number of prenatal visits, type of delivery and pregnancy. Contributions to practice: the study allows health professionals and managers to have more knowledge about the repercussions of teenage pregnancy, as well as the clinical and social outcomes in maternal and child health, such as prematurity, enabling more precise targeting of actions and programs aimed at this problem.